Evaluasi Pembelajaran Bahasa Arab Berbasis Teknologi Digital - Muhammad Azhar; Marlina Rahmawati; Hikmah; M. Ripani Saputra; Resy Mulyani; Siti Nurdinah; Angga Frananda; Fitri, Lidia (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
The primary objective of this research is to examine digital technology that can be used in Arabic language learning evaluation. The research method employed is a literature review by analyzing relevant scientific articles from indexed journals. The findings reveal that several digital technology, such as Edmodo, Quizizz, Google Forms, Kahoot, Plickers, and Thatquiz, possess unique features that support the learning evaluation process. The use of digital technology has been proven to improve time efficiency, accessibility for students, and learning motivation through an interactive approach. Additionally, the integration of digital technology in evaluation enables personalized learning, resource efficiency, long-term data management, and the development of digital skills for both students and educators. The implications of this study indicate that integrating digital technology into the evaluation of Arabic language learning can enhance teaching quality and responsiveness to students' needs. The main contribution of this research is to provide educators with a guide for selecting and implementing appropriate digital evaluation technologies.